2016
DOI: 10.1038/cddis.2016.265
|View full text |Cite
|
Sign up to set email alerts
|

Omentin protects against LPS-induced ARDS through suppressing pulmonary inflammation and promoting endothelial barrier via an Akt/eNOS-dependent mechanism

Abstract: Acute respiratory distress syndrome (ARDS) is characterized by increased pulmonary inflammation and endothelial barrier permeability. Omentin has been shown to benefit obesity-related systemic vascular diseases; however, its effects on ARDS are unknown. In the present study, the level of circulating omentin in patients with ARDS was assessed to appraise its clinical significance in ARDS. Mice were subjected to systemic administration of adenoviral vector expressing omentin (Ad-omentin) and one-shot treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 49 publications
3
58
0
1
Order By: Relevance
“…It is important to identify the upstream regulatory molecules associated with IQGAP1. According to some studies, the PI3K/Akt pathway is not only a crucial regulatory molecule for various cellular functions, but also important in transduction signalling underlying endothelial barrier function during sepsis . In the present study, we found that SV/SV‐NPs activated the PI3K/Akt pathway and promoted Akt phosphorylation, which was inhibited by LPS.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is important to identify the upstream regulatory molecules associated with IQGAP1. According to some studies, the PI3K/Akt pathway is not only a crucial regulatory molecule for various cellular functions, but also important in transduction signalling underlying endothelial barrier function during sepsis . In the present study, we found that SV/SV‐NPs activated the PI3K/Akt pathway and promoted Akt phosphorylation, which was inhibited by LPS.…”
Section: Discussionsupporting
confidence: 65%
“…According to some studies, the PI3K/Akt pathway is not only a crucial regulatory molecule for various cellular functions, but also important in transduction signalling underlying endothelial barrier function during sepsis. [50][51][52][53] In the present study, we found that SV/SV-NPs activated the PI3K/Akt pathway and promoted Akt phosphorylation, which was inhibited by LPS. We then used the PI3K inhibitor LY294002 to determine whether the PI3K/Akt pathway had a mediating function in SV/SV-NPs-induced barrier protection.…”
Section: Discussionsupporting
confidence: 58%
“…Omentin, another anti‐inflammatory adipokine that has decreased secretion in obesity, also reduces the damage of acute lung injury (Qi et al . ).…”
Section: Vascular Function In Obesitymentioning
confidence: 97%
“…In addition, Song et al administered omentin every 2 weeks for a total of 8 weeks via tail vein injection of an adenoviral vector to obese mice followed by the determination of produced proinflammatory cytokines 2 weeks after the last treatment [32]. In contrast, we measured the levels of proinflammatory biomarkers after the treatment of primary human adipocytes with recombinant omentin for 24 h. Other reasons for the differences might be that Rao et al [31] used an inflammatory cell model by treating macrophages with TNF-α and that in the study of Qi et al [33] mice were treated with LPS 3 days after omentin injection. In contrast, we investigated the effect of omentin without a previous or additional proinflammatory stimulus on the secretory process of primary human adipocytes.…”
Section: The Omentin-induced Secretion Profile Indicates a Proinflammmentioning
confidence: 98%
“…The same study evaluated the role of omentin in inflammation using an omentin knockout mouse model and showed that the depletion of omentin led to an increase in serum concentrations of IL-1α, TNF-α, and IL-6 [31]. Two additional studies indicated that omentin diminished the levels of proinflammatory cytokines and chemokines including IL-6 and TNF-α in the serum of obese mice [32] or in the lung tissue of LPStreated mice [33]. Thus, these findings argue rather for anti-inflammatory effects of omentin.…”
Section: The Omentin-induced Secretion Profile Indicates a Proinflammmentioning
confidence: 99%